PENGARUH KOMPETENSI MANAJER PROYEK TERHADAP KEBERHASILAN PROYEK PADA PERUSAHAAN KONTRAKTOR DI KABUPATEN MALANG - Prianto, Khusnul; Dewi, Sri Murni; Pujiraharjo, Alwafi (Media Teknik Sipil, 2012)
Khusnul Prianto1, Sri Murni Dewi2 & Alwafi Pujiraharjo31, 2 & 3Fakultas Teknik Jurusan Teknik Sipil Universitas Brawijaya MalangAlamat Korespondensi : Jl. MT. Haryono No 167 Malang, Indonesiaazdotagroup@yahoo.comABSTRACTThis study aims to determine how big a role simultaneously and partially between knowledge,skills and attitude of the project manager to project success, and to know the most dominant factorthat affects the success of a project. This research uses survey research conducted at contractorcompanies in Malang. The population in this study is the management of the contractor as theproject manager supervisor leader contractor (director) or authorized by the company. Primary datawas collected through questionnaires. Secondary data obtained from the literature to form iteratur,journals, and data from agencies with an interest in this study, such as professional associations andrelated agencies.The results of descriptive analysis using respondents’ answers showed knowledge variable,variable skills, attitudes and behavior / work commitment, top management variables on averagehave an important influence to determine the success of the project. Test results using regressionanalysis and test assumptions Multiple Linear Regression analysis shows simultaneously betweenthe variables of knowledge, skills, work commitment and top management significantly influencethe success of the project amounted to 0.831. Partially between the variables of knowledge, skills,work commitment and top management significantly influence the success of the project amountedto 0.286, 0.296, 0.280 and 0.147.Dominant variable affecting the level of success of a project is a skill / expertise.Keywords: Competence, Project Manager, Contracting Company